Modified Epoxy for Fibre Reinforced Polymer Strengthening of Concrete Structures - Abdullah, Siti Radziah; Rosli, Farah Nurhabibah; Ali, Noorwirdawati; Abd Hamid, Noor Azlina; Salleh, Norhafizah (International Journal of Integrated Engineering, 2020)
Fibre-Reinforced Polymer (FRP) is a preferable material for repairing concrete structure due to excellent material properties and effective installation cost over the long-term maintenance of structures. The successful application of FRP strengthening system very much depends on the bond between the concrete substrate and the FRP material using epoxy adhesive. Epoxy acts as a bridge to transfer stress from the concrete to the FRP material. The use of wet lay-up technique to apply FRP onto concrete structure requires epoxy to undergo a curing process normally referred to as cold curing. This paper intends to give a review of the problems with cold-cured epoxy and its effect on structural performance. Cured epoxy is characterised as brittle; therefore, modifications of epoxy are required to toughen the epoxy to suit the purpose of repairing a concrete structure. The methodological approaches from previous studies on modified epoxy were collected and reviewed in this paper. This review also offers some important insights regarding the use of sustainable materials, as well as recommendations for new epoxy in the future.